Factors controlling nanosized Ni–Al2O3 catalysts synthesized by solution combustion for slurry-phase CO methanation: the ratio of reducing valences to oxidizing valences in redox systems. Issue 21 (26th September 2016) - Gao, Yuan; Meng, Fanhui; Li, Xin; Wen, John Z.; Li, Zhong
Abstract : The ratio of urea to nitrates was investigated with regard to the precursor solution, combustion process, and Ni-Al2 O3 catalyst structures and activity. Abstract : A series of nanosized Ni–Al2 O3 catalysts for the catalytic methanation of CO were prepared by solution combustion of Ni 2+ and Al 3+ nitrates with urea. The main influence of the combustion process on the physicochemical and catalytic properties of Ni–Al2 O3 catalysts were investigated by using the RV/OV ratio of reducing valences from urea to oxidizing valences from nitrates in redox systems. With increasing RV/OV ratio, more urea molecules coordinate with Ni 2+ to form nickel ammine and enhance the diffusion of Ni 2+ in the precursor solution. During the combustion process, the combustion enthalpy and gases increase with increasing RV/OV value, operating synergistically to achieve controlled physicochemical properties of the obtained catalysts. Especially, when RV/OV ≤ 0.75, the released gases are critical to the formation of a high surface area to disperse the NiO nanoparticles, whereas when RV/OV ≥ 0.75, the combustion enthalpy produces a high temperature, facilitating NiO migration into the Al2 O3 matrix to form the low activity precursor NiAl2 O4 spinel. The catalyst with RV/OV = 0.75 exhibits the maximum nickel surface area and the smallest Ni particle size of 62.6 m 2 g −1 and 10.8 nm, respectively, which result in the optimum catalytic activity.